Pengaruh Spirulina terhadap Kadar beta hCG Tikus Bunting yang Diinduksi Interleukin-6 (Studi Bahan Biologis Tersimpan) - Harry K Gondo; Elizabeth Haryanti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
Preeclampsia is multisystem specific disorder in pregnancy. Preeclampsia characterized by increased cytokine Interleukin-6 and β hCG (human Chorionic Gonadotropin). Spirulina is green-blue alga contain antioxidant, vitamin, mineral. Spirulina has a potential effect as antiinflammation. The aim of this research was to know effect of spirulina to repair trophoblast at β hCG level of pregnant rats with preeclampsia condition (biology material collecting). The type of this research is an experimental laboratory with post-test only control group design. Preeclampsia models induced by Interleukin-6. Twenty-five rats were grouped to five group: Control, Control Positive, Spirulina dose 10, 20, and 40 mg/day, at the end of treatment, β hCG level were analyzed. Statistical analysis was used by one-way ANOVA. The results of this study showed that β hCG level of group spirulina dose 10 mg/day (85.11 ± 25.70 mIU/ml) did not significantly different (p=0.353), with group Dose 20 mg/day (79.65 ± 10.65 mIU/ml). Level of β hCG in Spirulina group dose 40 mg/day were 93.28 ± 17.12 mIU/ml. The spirulina groups dose 10 mg/day and dose 40 mg/day did not show significantly different level of β hCG (0.730> 0.05). Administration of spirulina at a dose of 10 mg was able to significantly reduce levels of β hCG (P <0.05) than at doses of 20 mg / day and 40 mg/ day.